Introduction to Special Issue: Development, Learning and Education. Post-pandemic Considerations? (NorDev21). Issue 1 (2nd January 2023) - Kontinen, Tiina; Steiler, Ilona
Abstract : This Introduction to special issue provides a context for the Nordic Development Research Conference 2021 (NorDev21). It introduces the contents of the conference and contributions within the issue revolved around two main themes of (1) Learning, education, Covid-19 pandemic and decolonizing and (2) State, Democracy, and Citizenship.